Natural Resources and Livestock Development in Surat District Submitted to Agro-Climatic Regional Planning Unit - Planning Commission (Planning Commission, 1992)
This study was done at the behest of the Agro- climatic Regional Planning Unit of the Planning Commission, The objective was to suggest ways of incorporating the livestock related features of a region in the regionalisation scheme, if warranted by the ground realities, operationalising the regionalisation scheme and demonstrating that meaningful policy prescriptions can result by so doing.
Agro-climatic Regional Planning Unit, Planning Commission, Government of India
Agro-climatic Regional Planning Unit, Planning Commission, Government of India